Hak Asasi Manusia dalam Dua Lensa: Komparasi Filosofis dan Prinsip Antara Perspektif Internasional dan Islam - elkarimah, Mia Fitriah (Tasyri' : Journal of Islamic Law, 2025)
This study explores the philosophical foundations, principles, and  comparisons of human rights from an international perspective (Universal Declaration of Human Rights/UDHR) and Islam (sourced from Medina Charter, and Cairo Declaration). Through literature review and descriptive-comparative analysis , it was found that although both perspectives acknowledge the inherent dignity of humans and basic rights, there are fundamental differences in the sources (natural dignity vs. divine revelation) and limitations of rights (e.g., related to freedom of religion and expression). Historically, both Western and Islamic traditions have developed frameworks for the protection of rights, with the Medina Charter as an early progressive document in the context of pluralism. The dynamics of modern human rights enforcement reveal a paradox between universalism and cultural relativism. However, through dialogue and harmonization—particularly through flexible reinterpretation of Islamic concepts such as ijtihad—it is possible to bridge these differences. This study concludes that the recognition and implementation of human rights can be strengthened globally and in the Islamic world, encouraging cross-cultural cooperation for equitable and sustainable social development.